2022
DOI: 10.1021/acs.orglett.2c01149
|View full text |Cite
|
Sign up to set email alerts
|

Ring-Opening Fluorination of Isoxazoles

Abstract: A ring-opening fluorination of isoxazoles has been developed. Upon treatment of isoxazoles with an electrophilic fluorinating agent (Selectfluor), fluorination followed by deprotonation leads to tertiary fluorinated carbonyl compounds. This method features mild reaction conditions, good functional group tolerance, and a simple experimental procedure. Diverse transformations of the resulting α-fluorocyanoketones were also demonstrated, furnishing a variety of fluorinated compounds.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…The tests carried out without a base were unsuccessful suggesting that the oxamate fragment of EtHL 2 does not undergo any acidic hydrolysis promoted by [Cu(bpca)(H 2 O) 2 ]NO 3 •2H 2 O as previously observed in other oxamate-based ligands. 84 The reason for the poor yield of 5 is attributed to the use of a strong base for the hydrolysis of the ester, which also causes the isoxazole ring opening, 74,85 resulting in a red-colored solution. Additionally, the amount of base for this reaction was enough to hydrolyze the ester and deprotonate the amide group, leading to the dianionic oxamate group ([L 2 ] 2− ), which is able to adopt the bis(bidentate) coordination mode [μ-oxamato-κ 2 N,O:κ 2 O′,O″].…”
Section: Resultsmentioning
confidence: 99%
“…The tests carried out without a base were unsuccessful suggesting that the oxamate fragment of EtHL 2 does not undergo any acidic hydrolysis promoted by [Cu(bpca)(H 2 O) 2 ]NO 3 •2H 2 O as previously observed in other oxamate-based ligands. 84 The reason for the poor yield of 5 is attributed to the use of a strong base for the hydrolysis of the ester, which also causes the isoxazole ring opening, 74,85 resulting in a red-colored solution. Additionally, the amount of base for this reaction was enough to hydrolyze the ester and deprotonate the amide group, leading to the dianionic oxamate group ([L 2 ] 2− ), which is able to adopt the bis(bidentate) coordination mode [μ-oxamato-κ 2 N,O:κ 2 O′,O″].…”
Section: Resultsmentioning
confidence: 99%
“…Numerous examples of catalytic hydrogenation of isoxazole derivatives are reported in the literature. Among them, in most cases the isoxazole ring is not affected by hydrogenolysis under mild conditions using palladium as a metal catalyst (for representative examples of debenzylation, nitro group reduction, and double bond hydrogenation see page 2297 of [5], page 5/6 of [6], and page S14 of [7]), and only in some cases the ring opens to give an enaminone [8].…”
Section: Resultsmentioning
confidence: 99%
“…Very recently, the same group extended this chemistry to another heteroaromatic compound, isoxazoles (Figure 15). [31] Isoxazoles 48 with a variety of substituents at C4 and C5 positions smoothly reacted to afford the corresponding products 49 . Derivatization of the products showed that this method can construct diverse tertiary fluorine‐containing skeletons, which are difficult to synthesize by conventional methods.…”
Section: Ring‐opening Fluorination Of Aromatic Compoundsmentioning
confidence: 99%